(untitled) (Global Journal of Medical Research, 2022)
Objectives: To show that combining neuro-urological examinations in the lumbosacral area permit to refine the neurological diagnosis by evaluating ascending and descending spinal cord pathways, sacral reflex arcs and the status of the related muscles. Setting: University Antwerp Belgium. Methods: Evaluation of perineal sensation with light digital touch (SENSPER), anal sphincter tone(AST) and voluntary contraction (ASC), anal reflex (ASR), bulbocavernosus reflex (BCR) were done in patients with SCI as part of pre urodynamic testing. Results: 121 individuals were included, 80 males and 41 females, age 46 ± 16 years old, with different levels and completeness of SCI, determined with ASIA/ISCoS International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI). The examination was done 6.6 ± 12 years post lesion. The findings did not differ between gender or age, except that ASR was more frequently absent in women and ASC diminished with increasing age.